Green Asset Digital Development through a Pentahelix Approach in Green Waqf: Tackling Poverty and Improving Prosperity - Putri Utari, Diana; Wardatul Umah, Lia; Dhafa Irvani, Anggia; Andani, Listia; Zaki Ibrahim, Hilmi (UIN Sunan Gunung Djati Bandung, 2025)
This research aims to analyze the strategy of developing digital green assets in green waqf with a pentahelix approach. Through this strategy, poverty and challenging environmental issues can be addressed by ensuring a balance between economic development and environmental preservation. This research uses descriptive-qualitative analysis method and literature study to explore in-depth understanding of the strategy of developing green digital assets in green waqf, and identify how the pentahelix approach is able to develop the strategy. The results and discussion identify that the pentahelix model is able to play a key role in developing green digital assets in green waqf, where the pentahelix model relates to cooperation between government, academia, business, community and media. Green waqf can be started by raising funds through a crowdfunding mechanism, then channeled to empower damaged forests with the aim of restoring them to green forests to have ecological value, which will then be endowed for the benefit of the community. The conclusion of this research is that the strategy of developing digital green assets in green waqf using the pentahelix approach can be a solution to alleviate poverty and improve welfare. However, there are still some challenges faced regarding the potential of waqf in Indonesia, such as the lack of professionalism of nazirs, low public waqf literacy, and not optimal education and socialization of green waqf.